2017
DOI: 10.1021/acs.jafc.7b00327
|View full text |Cite
|
Sign up to set email alerts
|

Hot-Water Extracts from Roots of Vitis thunbergii var. taiwaniana and Identified ε-Viniferin Improve Obesity in High-Fat Diet-Induced Mice

Abstract: In this study, hot-water extracts (HW) from roots of Vitis thunbergii var. taiwaniana (VTT-R) were shown to lower levels of lipid accumulation significantly (P < 0.01 or 0.001) compared to the control in 3T3-L1 adipocytes. The VTT-R-HW (40 mg/kg) interventions concurrent with a high-fat (HF) diet in C57BL/6 mice over a 5 eek period were shown to reduce body weights significantly (P < 0.05) compared to those of mice fed a HF diet under the same food-intake regimen. The (+)-ε-viniferin isolated from VTT-R-HW was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 43 publications
0
14
0
Order By: Relevance
“…In other studies, ε-viniferin decreased the accumulation of lipids and inhibited of the enzyme HMG-CoA reductase, an enzyme involved in cholesterol synthesis, for a concentration range of 2.5 to 50 µM in 3T3-L1 adipocytes [ 12 , 13 ]. Thus, despite the weak adipose concentrations of ε-viniferin observed in our study as compared to those reported to exert an anti-adipogenic effect in vitro, we believe they are sufficient to induce an anti-adipogenic effect in vivo.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…In other studies, ε-viniferin decreased the accumulation of lipids and inhibited of the enzyme HMG-CoA reductase, an enzyme involved in cholesterol synthesis, for a concentration range of 2.5 to 50 µM in 3T3-L1 adipocytes [ 12 , 13 ]. Thus, despite the weak adipose concentrations of ε-viniferin observed in our study as compared to those reported to exert an anti-adipogenic effect in vitro, we believe they are sufficient to induce an anti-adipogenic effect in vivo.…”
Section: Discussionmentioning
confidence: 98%
“…Moreover, studies mentioned above also reported that an oral administration of ε-viniferin was found to limit weight gain in mice fed a hypercaloric diet without decreasing their food intake. The authors explained the weight loss by a decrease in the mass of mesenteric white adipose tissue [ 12 , 13 ]. This suggests that the rage of concentrations found in adipose tissue in our study may be responsible for the effect observed in studies in mice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The hot water extracts of root parts of Vitis thunbergii var. taiwaniana and the isolated ε‐viniferin, 8 as well as the chloroform‐partitioned fraction of hot‐water extracts of Cucurbita moschata and its isolated dehydrodiconiferyl alcohol, 9 showed anti‐adipogenic effects with respect to reducing lipid accumulations in Oil Red O (ORO)‐stained differentiated 3 T3‐L1 adipocytes.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, εVin is also promising for its anti-adipogenic properties insofar as it has been shown that this compound decreased lipid accumulation and adipogenesis marker gene expression such as Peroxisome Proliferatoractivated Receptor gamma (PPAR ϒ ) in a 3T3-L1 adipocytes cell line [29]. The decrease in body weight gain in rat fed with a high fat diet and the reduction of the mass of white adipose tissues in mice after oral administration of εVin [29,30] highlight its potential in vivo biological activities. These interesting properties lead to asking the question of its fate in the systemic circulation after ingestion.…”
Section: Introductionmentioning
confidence: 99%